Assessment of Breastfeeding Practices among Mothers with Babies up to 6 Months of Age - Rujvee P Patel; Prakash Patel; Neeta Sharma; Swati Patel (Medsci Publications, 2020)
Introduction: Breastfeeding is one of the most effective ways to ensure child health and survival. The study was conducted to assess knowledge and practices of breastfeeding in mothers with babies up to 6 months of age in Surat, Gujarat, India. Method: A cross sectional study was carried out to assess the knowledge and practices of Exclusive Breastfeeding (EBF) among postpartum mothers attending immunization clinics at a Government Health Centre and affiliated Aanganwadis in Surat, Gujarat, India in the months of August to November 2019. Data was collected through face-to-face interviews using a structured questionnaire. Results: In our study, it is observed that out of a total of 97 mothers, 73.20% (n=71) mothers are aware about the concept of Exclusive Breastfeeding, while only 52.58% (n=51) practice EBF. Adequate number of mothers were aware about the benefits of breast milk to the baby. Conclusion: The knowledge and awareness regarding benefits of breastfeeding to the mothers, methods and criteria for breastfeeding and contraindications of breastfeeding still remains substandard.